Metformin prevents hepatocellular carcinoma development by suppressing hepatic progenitor cell activation in a rat model of cirrhosis. Issue 8 (23rd February 2016) - DePeralta, Danielle K.; Wei, Lan; Ghoshal, Sarani; Schmidt, Benjamin; Lauwers, Gregory Y.; Lanuti, Michael; Chung, Raymond T.; Tanabe, Kenneth K.; Fuchs, Bryan C.
Abstract : BACKGROUND: Hepatocellular carcinoma (HCC)‐associated mortality is increasing at an alarming rate, and there is a readily identifiable cohort of at‐risk patients with cirrhosis, viral hepatitis, nonalcoholic fatty liver disease, and diabetes. These patients are candidates for chemoprevention. Metformin is an attractive agent for chemoprevention because it is inexpensive, has a favorable safety profile, and is well tolerated over long time periods. METHODS: The authors studied the efficacy of metformin as a prevention agent in a clinically relevant rat model of HCC, in which tumors develop in the setting of chronic inflammation and cirrhosis. Repeated injections of diethylnitrosamine were used to induce sequential cirrhosis and HCC, and metformin was administered at the first signs of either fibrosis or cirrhosis. RESULTS: Prolonged metformin exposure was safe and was associated with decreases in fibrotic and inflammatory markers, especially when administered early at the first signs of fibrosis. In addition, early metformin treatment led to a 44% decrease in HCC incidence, whereas tumor burden was unchanged when metformin was administered at the first signs of cirrhosis. It is noteworthy that activation of the hepatic progenitor/stem cell compartment was first observed at the onset of cirrhosis; therefore, only early metformin treatment suppressed receptor for advanced glycation end products and inhibited the activation of hepatic progenitor cells. CONCLUSIONS: The current results are the first to demonstrate an effect on progenitor/stem cells in the setting of chemoprevention and provide further rationale to explore metformin as an early intervention in clinical trials of patients with chronic liver disease at high risk for HCC. Cancer 2016;122:1216–27 . © 2016 American Cancer Society . Abstract : This is the first report to demonstrate that chemopreventive effects of metformin are mediated through progenitor/stem cells. The results provide further evidence that early and long‐term treatment with metformin is a promising strategy for the prevention of tumors in the liver: its main site of action.